1967
DOI: 10.1113/expphysiol.1967.sp001934
|View full text |Cite
|
Sign up to set email alerts
|

Daily Rhythms of Renal Excretion in Arctic‐dwelling Indians and Eskimos

Abstract: The daily rhythms of renal excretion of indigenous arctic subjects were recorded under natural conditions during the continuous midsummer daylight (Indians and Eskimos) and in the continuous darkness of midwinter (Indians only). The excretory patterns for water, potassium, sodium and chloride have been compared with those of a group of British control subjects, recorded when they were newly introduced into a summer arctic environment in adult life. In general, the excretory patterns of the arctic subjects cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…No circadian pattern of melatonin or cortisol secretion in Weddell seals was apparent under natural, Antarctic summer conditions (Barrell and Montgomery 1989). Even Eskimos are reported not to show the regular 24-hour periodicity of urine production and potassium excretion (Lobban 1967) and in European volunteers of Svalbard (Spitzbergen) synchronization of the circadian system did not take place supposedly because of the weakness of the Zeitgeber (Johnson et al 1979). On the evidence of these publications neither the sun nor cyclic fluctuations in the vertical component intensity of the earth's magnetic field, as suggested by Bliss and Heppner (1976) must have been strong or clear enough clues to set up and maintain circadian rhythms.…”
Section: Discussionmentioning
confidence: 97%
“…No circadian pattern of melatonin or cortisol secretion in Weddell seals was apparent under natural, Antarctic summer conditions (Barrell and Montgomery 1989). Even Eskimos are reported not to show the regular 24-hour periodicity of urine production and potassium excretion (Lobban 1967) and in European volunteers of Svalbard (Spitzbergen) synchronization of the circadian system did not take place supposedly because of the weakness of the Zeitgeber (Johnson et al 1979). On the evidence of these publications neither the sun nor cyclic fluctuations in the vertical component intensity of the earth's magnetic field, as suggested by Bliss and Heppner (1976) must have been strong or clear enough clues to set up and maintain circadian rhythms.…”
Section: Discussionmentioning
confidence: 97%
“…There 20 Ofo of the persons had long-standing peptic disorders, and 10 Ofo had been away from work for this reason. We found peptic ulcers ,in 13 Ofo 'and gastritis in [26][27][28][29] 11/0, respectively. 'I1his frequency its higher than what has been found for other groups, e.g., dock workers (30), but it is in accord with the findings of Bjerner et al (6), who found that traveling railroad personnel had more peptic ulcers ,than Swedes in general.…”
Section: Discussionmentioning
confidence: 99%
“…In animals ,the change from light to darkness and fmm darkness to light is a very strong synchronizer (19) or "Zettgeber" (4). In man, on Ithe other hand, sociarl rellatoons !Seem <to be stiN more impontlant (6,27). A great number of social complication!S wel'e .reported in shift workers when the family and community followed a daytime pattern (32).…”
mentioning
confidence: 99%
“…The daily rhythms of renal excretion of indigenous arctic Indians and Eskimos have been described in detail elsewhere (Lobban, 1967). Briefly, abnormalities occurred relatively frequently in the excretory rhythms of these arctic-dwellers, such that although in the averaged patterns for indigenous arctic communities temporal relationships similar to those of control (temperate zone) groups were maintained, the peak to trough range and relative amplitude of the rhythms were reduced.…”
Section: Time Of Day In Hoursmentioning
confidence: 99%